Control Synthesis for Marine Vessels in Case of Limited Disturbances - Mikhail Smirnov; Maria A. Smirnova (Universitas Ahmad Dahlan, 2018)
In view of rapid development of computer technology digital systems of automatic control are installed on the modern marine vessels for performance of various manoeuvres at optimal trajectories taking into account features of the ship and active disturbances. In this connection, great number of problems that deal with construction of automatic control systems, such as minimizing the fulfillment time of the maneuver, searching for the optimal trajectory, the suppression of various types of exogenous disturbances like wind and rough sea, arises. In the work, the problem of suppression of exogenous disturbances acting on a marine vessel, about which we have no information except its boundedness, is considered. The problem of searching of the controller as a static state feedback is the basis of offered approach. The system MATLAB-Simulink is accepted as the basic tool of the computer support. An example of modeling control system for the carrier is presented.